Shame on You! When and Why Failure-Induced Shame Impedes Employees’ Learning From Failure in the Chinese Context - Wang, Wenzhou; Song, Shanghao; Wang, Jiaqi; Liu, Qi; Huang, Lishi; Chen, Xiaoxuan (Frontiers in Psychology, 2021)
The emotional experience brought about by failure, especially the important roles of negative emotions in learning behavior after failure, has received increasingly more attention from organization management scholars. Research on the impact of employees’ sense of failure-induced shame is still controversial. Based on the Chinese context, according to the process model of emotion regulation theory, we have studied the influence of failure-induced shame on employees’ learning from failure and the conditions that have boundary effects on this process. Through a questionnaire analysis of 776 samples from Chinese high-tech enterprises, the results show the following: (1) shame has a negative relationship with learning from failure, (2) project commitment alleviates the negative relationship between shame and learning from failure, and (3) restoration orientation alleviates the negative relationship between shame and learning from failure while loss orientation cannot. Our results further enrich the research on negative emotions related to failure and provide a theoretical basis for the failure management of Chinese companies.